2014
DOI: 10.3389/fped.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Outcome in Hypospadias Surgery – A Review

Abstract: Hypospadias is a challenging field of urogenital reconstructive surgery with different techniques being currently used. Modern surgery claims that it is possible to create a functionally and cosmetically normal penis. Continuous re-evaluation and assessment of outcome may have a major impact on future clinical practice. Assessment of outcome includes: complication rate, cosmetic appearance of the penis, functional outcome (micturition, sexuality), and psychological factors such as quality of life and psychosex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Surgeon perceptions and reporting of complication rates may also differ,14 and there would seem conflicting information about the timeframe of occurrence of complications to determine an ideal follow-up period 15. A recent survey of surgeons reported that nearly 60% follow-up their patients for <6 months,16 yet studies suggest that nearly half of complications may only be diagnosed after the first year following surgery 17. Current information on population-based hypospadias’ prevalence, trends, rates of surgical repairs and follow-up of health outcomes appears highly important for optimal clinical decision-making treatment, management and preoperative counselling of parents.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeon perceptions and reporting of complication rates may also differ,14 and there would seem conflicting information about the timeframe of occurrence of complications to determine an ideal follow-up period 15. A recent survey of surgeons reported that nearly 60% follow-up their patients for <6 months,16 yet studies suggest that nearly half of complications may only be diagnosed after the first year following surgery 17. Current information on population-based hypospadias’ prevalence, trends, rates of surgical repairs and follow-up of health outcomes appears highly important for optimal clinical decision-making treatment, management and preoperative counselling of parents.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of papers did not address the issue of if the boys were lost to follow-up or excluded from the study. It has to be assumed that the follow-up rate usually is 100% as is the case in our group of boys [20].…”
Section: -mentioning
confidence: 91%
“…Given that nephron progenitors are critical in establishing final nephron endowment, these progenitors must maintain their ability to self-renew so as to prevent premature exhaustion prior to cessation of nephrogenesis (7,9,19,20). Moreover, incorrect differentiation of nephron progenitors leads to renal dysplasia (21). …”
Section: Introductionmentioning
confidence: 99%
“…Nephron patterning into the various highly specialized segments is essential for establishing the functional role of the nephron, and abnormalities of nephron pattern result in renal dysplasia (21). Progression of pretubular aggregates into polarized renal vesicles is dependent on the hierarchal expression of Fgfrl1, Fgf8, Wnt4 and Lhx1 (33-36).…”
Section: Introductionmentioning
confidence: 99%